Translation as Politics: Translating Nikolai Karamzin’s Letters of a Russian Traveler in Nineteenth-Century France - Rodolphe Baudin (Вивліоѳика)
This article examines the three translations of Nikolai Karamzin’s Letters of a Russian Traveler published in nineteenth-century France. Relying on Descriptive Translation Studies so as to challenge the traditional narrative about the political innocuousness of Karamzin’s travelogue, it reconstructs the historical contexts of the three publications in order to highlight the political agendas of their translators and/or translating patrons. Far from being the innocent product of the translators’ sheer curiosity, the three translations prove to be political objects, used at three key moments in the history of Franco-Russian relations in the nineteenth century, in order to call for political change, to try and restore Russia’s damaged reputation, or to attempt to forge new diplomatic alliances.